Multicomponent Dietary Supplementation: Impact on Tear Secretion and Ocular Surface Inflammation in Dry Eye Syndrome Patients - Shih-Chien Huang; Yen-Ping Lei; Min-Chien Hsiao; Yu-Kai Hsieh; Quei-Ping Tang; Connie Chen; Min-Yen Hsu (Antioxidants)
Dry eye syndrome (DES) is a prevalent ocular condition characterized by tear film instability, inflammation, and discomfort, affecting millions worldwide. DES is related to oxidative stress imbalance and ocular surface inflammation, which are important factors in the development of the condition. Recent studies have demonstrated that fish oil, lutein, and zeaxanthin possess anti-inflammatory and antioxidant properties. This study investigated the efficacy of a multicomponent dietary supplement in improving tear secretion and mitigating ocular surface inflammation in patients with DES. It was an open-label intervention trial. In total, 52 participants were randomly assigned to control (n = 23) and supplement (45 mg/day eicosapentaenoic acid, 30 mg/day docosahexaenoic acid, 30 mg/day lutein, and 1.8 mg/day zeaxanthin; n = 29) groups for 12 weeks. The participants were evaluated using Schirmer’s test and the ocular surface disease index (OSDI) as ocular surface parameters. Moreover, blood or tear oxidative stress, antioxidant capacities, and tear inflammatory indicators were measured at weeks 0 and 12. The results indicated a significant increase in tear secretion and a significant reduction in OSDI scores in the supplement group. Additionally, inflammatory markers, such as interleukin (IL)-6 and IL-8, significantly decreased after the intervention. However, the OSDI of the supplement group significantly improved by 6.60 points (β = −6.60, p = 0.01). These findings support the potential of targeted nutritional supplementation as a safe and effective strategy for alleviating DES symptoms, offering an alternative to conventional treatments that exclusively focus on symptom management. This study highlights the role of specific nutrients in modulating tear production and inflammation, thereby providing a foundation for dietary approaches to DES treatment. Future research should explore the long-term benefits of such interventions and their impact on overall ocular health.